A service evaluation describing a nurse‐led prostate cancer service in NHS, Ayrshire and Arran. Issue 3 (18th July 2014) - McGlynn, Brian; White, Lillian; Smith, Kathleen; Hollins, Graham; Gurun, Murat; Little, Brian; Clark, Ross; Nair, Biju; Glen, Hilary; Ansari, Jawaher; Mahmood, Rana; Nairn, Robert; et al.
ABSTRACT From 1999, the NHS Ayrshire and Arran Health Board implemented an innovative nurse‐led collaborative care model for the management of patients with prostate cancer (PC). This article describes the model and presents the results of a local evaluation to assess its impact. The evaluation comprised a retrospective audit of the service against national standards for PC management, undertaken in 2012. Seventy‐one patients, who were under the care of the service during June 2008, were included. Patient and staff satisfaction were also assessed using questionnaires distributed to 75 patients undergoing outpatient or telephone reviews during April 2012 and 7 one‐to‐one semi‐structured staff interviews. The patient audit showed good compliance with standards relating to selection of appropriate PC treatments according to tumour stage and grade; radiotherapy dosing and referral‐to‐treatment times. Areas requiring improvement were the documentation of patients' risk and performance status and provision of verbal and written information to patients and carers. Seventy‐three per cent of the patient questionnaires were returned, with 96% of respondents rating their overall care as 'excellent' or 'very good'. Staff satisfaction was also high and interviewees described many benefits of the service for patients, hospital staff, GPs and the NHS/health board. Negative responses related mainly to demand/capacity issues. Overall, the evaluation showed good compliance with many national standards and high levels of patient and staff satisfaction. This suggests that with trained and competent nursing staff and collaborative multidisciplinary team working, safe and appropriate care can be achieved for more complex, as well as very stable PC patients.